2013
DOI: 10.1007/s12272-013-0194-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of hydrogen sulfide against cold restraint stress-induced gastric mucosal injury in rats

Abstract: Hydrogen sulfide (H2S) is an endogenous gaseous mediator plays a potential role in modulating gastric inflammatory responses. However, its putative protective role remains to be defined. The present study aimed to evaluate role of the exogenously released and endogenously synthesized H2S in cold restraint stress (CRS)-induced oxidative gastric damage in rats. Rats were restrained, and maintained at 4 °C for 3 h. The H2S donor, sodium hydrosulfide (NaHS) (60 μmol/kg) was injected intraperitoneally (i.p.) before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In the dose range used in our present study NaHS exhibited vasodilatory properties as documented by dose-dependent increase in GBF that accompanied the protective activity of this compound suggesting that H 2 S is responsible for an increase in the GBF observed in our study. Our data are corroborative with recent report that NaHS administered intraperitoneally prevented cold restraint stress-induced oxidative gastric damage by the mechanism involving the inhibition of gastric acid and attenuation of reactive oxygen metabolites [ 31 ]. Lou et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the dose range used in our present study NaHS exhibited vasodilatory properties as documented by dose-dependent increase in GBF that accompanied the protective activity of this compound suggesting that H 2 S is responsible for an increase in the GBF observed in our study. Our data are corroborative with recent report that NaHS administered intraperitoneally prevented cold restraint stress-induced oxidative gastric damage by the mechanism involving the inhibition of gastric acid and attenuation of reactive oxygen metabolites [ 31 ]. Lou et al .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, using similar experimental model of stress-induced gastric lesions, Aboubakr et al . [ 31 ] demonstrated that the inhibition of key enzyme of H 2 S synthesis, CSE with beta-cyano-L-alanine (BCA) exacerbated stress-induced gastric damage.…”
Section: Discussionmentioning
confidence: 99%
“…Apply it to the model of gastric mucosa damage to explore the potential mechanisms of H 2 S. By summarizing the experiments, we found that the conclusions between the different experiments are inconsistent. According to some research,26272829303132 NaHS played a protective effect in gastric mucosa damage. NaHS could decrease hemorrhagic damage, edema and epithelial cell loss induced by ethanol 26.…”
Section: Experimental Studies Of Hydrogen Sulfide In Gastric Mucosa Dmentioning
confidence: 99%
“…NaHS played a protective role through modulation of adenosine triphosphate-sensitive potassium channel opening and through the NF-κB dependent pathway 2728. It could reduce the serum level of TNF-α and interleukin-1β to abrogate the inflammatory 2930. It significantly decreased ulcer area31 and increased gastric blood flow at ulcer margin 3032.…”
Section: Experimental Studies Of Hydrogen Sulfide In Gastric Mucosa Dmentioning
confidence: 99%
“…NaHS (an H 2 S donor) attenuated ulcer index by reduction of gastric acid output, mucosal carbonyl content, pepsin activity and ROS generation. H 2 S also reduced tumoral necrosis factor (TNF)-alfa and myeloperoidase activity [ 41 ]. Recently, an attenuation of protective and hyperemic activity of NaHS in rats has been shown following capsaicin denervation.…”
Section: Introductionmentioning
confidence: 99%